Contextualizing Wilson’s Information Behavior model in Seeking Indigenous Information for HIV prevention among Adolescents in Secondary schools, Uganda - Olivia Nina, Rugambwa; Lyaka, Martha; Mutibwa, Lois Nankya (DigitalCommons@University of Nebraska - Lincoln, 2021)
Effective communication of quality health information in emergency situations is critical in curbing the spread of diseases. Health programs promoting both biomedical and indigenous representations in HIV prevention have been found to be more effective than those that ignore lay representations. Nonetheless, there is still limited documentation on indigenous information supporting health choices among adolescents in secondary schools in Uganda. Besides, the information sources from where adolescents seek this information are not clear. This paper presents Wilson’s Information Behavior model as the theoretical anchor used to understand how utilization of Indigenous information can be enhanced among adolescents for improved health choices on HIV prevention. The model was used as part of a doctoral study project to study the problem and propose a research design. The key constructs of the model adopted for the study include; context of information need, person in context, activating mechanism, and information search behavior, information processing and use. These served as the blueprints for enhancing access and use of indigenous information for HIV prevention in a school setting.